The Effect Of Compression Ratio By Different Piston Head Shape On The Performance Of Motorcycle Engine - Katijan, Adnan; Kamardin, Azizul Hakim (Penerbit Universiti Malaysia Pahang, 2019)
The compression ratio has a significant impact on engine power, fuel economy, emission, and other performances of internal combustion engines. Basic engine theory states that a higher compression ratio produces higher torque and horsepower. One way of having different compression ratio is by changing piston head shape. A piston is a cylindrical engine component that slides back and forth in the cylinder bore via forces produced during the combustion process. The piston acts as a movable end of the combustion chamber transmitting power generated from the burning of fuel and air mixture in the combustion chamber. The objective of this study is to compare the engine performance in horsepower and torque produced by the different shapes of the piston head in an internal combustion engine. Three pistons with different head shapes - standard, mug (low compression) and dome (high compression) with a compression ratio of 8.8:1, 7.61:1 and 10.06:1 were selected for the study. An experiment was also performed to a standard piston installed with 1.5 mm gasket, which has a compression ratio of 7.31. The experiments were carried out using a standard internal combustion engine of a Honda EX5 motorcycle. The engine runs on a chassis dynamometer to measure its torque and horsepower. Piston performance was evaluated based on the maximum available torque and horsepower. The result shows that all three pistons produce different torque and horsepower. The domed piston head produces higher torque and horsepower followed by the standard and mug. By just changing the piston head shape, torque and horsepower increased up to 7.14% and 20.05% respectively.